A Focused Habitat Approach for Northern Bobwhite Restoration in Kentucky - John J. Morgan; John M. Yeiser; Danna L. Baxley; Gary Sprandel; Ben A. Robinson; Keith Wethington (National Quail Symposium Proceedings, 2017)
The Kentucky Department of Fish and Wildlife Resources has measured northern bobwhite (Colinus virginianus) population trends since 1960. During that span, northern bobwhite steadily declined because clean agriculture, fescue-sod, plant succession, and development eroded habitat suitability. Multiple efforts have failed with regard to restoring northern bobwhite numbers. Over 3.5 million northern bobwhite were released by the Department over a three decade period. Habitat efforts on private lands were deployed for over 20 years with mixed results. Support for the habitat restoration efforts waned. In 2008, the Department unveiled a new strategy centered on restoring concentrated habitat in focal areas. From 2008 to 2013, the Department managed habitat and monitored breeding northern bobwhite on 5 focal areas that were distributed throughout the state. Focal areas ranged in size from 1,155 to 16,517 ha. A total of 109 breeding bird survey points were monitored annually with up to three repetitions. Habitat management activity was also tracked. We used distance sampling to model density-dependent and density-independent population growth. Across the study, there was a 0.992 probability that our populations were growing with a mean region-wide, density independent growth rate of 35.7% annually. We were able to grow populations in an array of landscapes that were dominated by agriculture and grasslands. Management actions maintaining ≥10% of the focus areas in early successional habitat consistently supported growing northern bobwhite populations. The unique nature of our focal areas made them poor laboratories for field study, so future multi-state collaboration may be essential to understand the factors driving northern bobwhite growth. A better understanding of northern bobwhite population growth as it relates to landscape, management, weather, and harvest metrics will improve management prescriptions for northern bobwhite habitat on larger landscapes in the future.
Keywords: Colinus virginianus; northern bobwhite; restoration; Kentucky; habitat